“Don't affect the share price”: social media policy in higher education as reputation management - Tony McNeill (Association for Learning Technology, 2012)
The last 5 years have seen a growing number of universities use social media services such as Twitter, Facebook and YouTube to engage with past, present and prospective students. More recently still, a number of universities have published policy or guidance documents on the use of social media for a range of university-related purposes including learning, teaching and assessment. This study considers the social media policies of 14 universities in the United Kingdom (UK) that are currently in the public domain. It addresses some of the ways in which Higher Education Institutions (HEIs) are responding to both the positive potential of social media as well as its perceived threats. Drawing inspiration, if not actual method, from critical discourse analysis, this study argues that marketisation has been the main policy driver with many social media policies being developed to promote university “brands” as well as protect institutional reputation. The creation and implementation of social media policies are therefore playing a role in helping universities manage both the risks and the benefits of social media in the context of an increasingly marketised Higher Education (HE) environment in which protecting institutional reputation has become a priority. However, in the defence of the metaphorical institutional “share price”, some policies constrain both academic autonomy and the possibilities for innovation and risk-taking.